Social Acceptance for Floating Houses as Alternative Residential in Coastal Area - Henny Pratiwi Adi; Jorge Jansen; Rick Heikoop (Universitas Islam Sultan Agung, 2020)
Semarang as a city located in the coastal area is dealing with the some problems, such as rising sea level, land subsidence, scarcity of land and illegal settlers. In order to deal with rising sea level, a polder system is developed in Kemijen (northern of Semarang). This polder system depends on dredging, a pumping station and retention basins to store water. To make the polder function well and reduce the floods, the existing retention basins should be expanded. Therefore, people who are living at the borders of these basins should be relocated or floating houses could be a solution.. This study aims to determine the acceptance of the Kemijen inhabitants towards floating houses as alternative residential in coastal areas. Data collecting in this study were obtained through interviews with the Kemijen residents and stakeholders. The data then processed by SWOT analysis. Based on the research result, it can be concluded that the social acceptance of the inhabitants is quite low, but there is potential because they see positive elements in a floating house. According to the survey most inhabitants do have insufficient income to pay for a floating house. Building on water is still not legal in Indonesia and therefore the law should probably be adjusted. Besides the land owner is still reluctant in building legal houses on its land. In order to improve the social acceptance of floating houses, these factors should be strengthening, namely relative advantages, compatibility, complexity, trialability and observability.